2000
DOI: 10.4049/jimmunol.165.6.3284
|View full text |Cite
|
Sign up to set email alerts
|

The Primate Lentiviral Receptor Bonzo/STRL33 Is Coordinately Regulated with CCR5 and Its Expression Pattern Is Conserved Between Human and Mouse

Abstract: Chemokines play necessary and important roles in regulating the trafficking of lymphocytes to intra- or interlymphoid tissues as well as to sites of inflammation. The complex migratory patterns of lymphoid lineage cells is governed by subset-specific expression of chemokine receptors and their access to specific ligands. Several chemokine receptors and chemokine receptor-like orphan receptors also serve, in conjunction with CD4, as coreceptors for infection by human and simian immunodeficiency viruses (HIV and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
157
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 193 publications
(174 citation statements)
references
References 58 publications
(56 reference statements)
14
157
3
Order By: Relevance
“…Previous studies demonstrated the expression of IL-15 on synoviocytes and synovial endothelial cells in RA (36,37). Although a few peripheral blood T cells expressed CXCR6 ( Figure 3A), stimulation with 30 ng/ml of IL-15 for 8 days significantly increased CXCR6 expression in vitro (for CD4, mean Ϯ SEM 30.2 Ϯ 6.5%; for CD8, 16.9 Ϯ 1.4% [P Ͻ 0.05]; n ϭ 5) compared with expression without IL-15 stimulation (for CD4, 4.0 Ϯ 1.0%; for CD8, 7.1 Ϯ 2.0%; n ϭ 5); these findings are similar to those previously reported (38). Although IL-15 stimulation upregulated CXCR6 expression by both CD154-negative and CD154-positive CD4 and CD8 T cells (for CD4, mean Ϯ SEM 18.1 Ϯ 5.7% and 32.8 Ϯ 10.5%, respectively; for CD8, 14.9 Ϯ 0.9% and 42.1 Ϯ 7.8%, respectively [P Ͻ 0.05]; n ϭ 3) compared with unstimulated T cells (for CD4, 0.5 Ϯ 0.1% and 2.0 Ϯ 2.0%, respectively; In order to analyze the functional effects of CXCL16 on IL-15-stimulated CXCR6-positive T cells, we analyzed the effects of CXCL16 on migration activity and IFN␥ production.…”
Section: Expression Of Cxcr6 By Cd4 and Cd8 T Cellssupporting
confidence: 89%
See 1 more Smart Citation
“…Previous studies demonstrated the expression of IL-15 on synoviocytes and synovial endothelial cells in RA (36,37). Although a few peripheral blood T cells expressed CXCR6 ( Figure 3A), stimulation with 30 ng/ml of IL-15 for 8 days significantly increased CXCR6 expression in vitro (for CD4, mean Ϯ SEM 30.2 Ϯ 6.5%; for CD8, 16.9 Ϯ 1.4% [P Ͻ 0.05]; n ϭ 5) compared with expression without IL-15 stimulation (for CD4, 4.0 Ϯ 1.0%; for CD8, 7.1 Ϯ 2.0%; n ϭ 5); these findings are similar to those previously reported (38). Although IL-15 stimulation upregulated CXCR6 expression by both CD154-negative and CD154-positive CD4 and CD8 T cells (for CD4, mean Ϯ SEM 18.1 Ϯ 5.7% and 32.8 Ϯ 10.5%, respectively; for CD8, 14.9 Ϯ 0.9% and 42.1 Ϯ 7.8%, respectively [P Ͻ 0.05]; n ϭ 3) compared with unstimulated T cells (for CD4, 0.5 Ϯ 0.1% and 2.0 Ϯ 2.0%, respectively; In order to analyze the functional effects of CXCL16 on IL-15-stimulated CXCR6-positive T cells, we analyzed the effects of CXCL16 on migration activity and IFN␥ production.…”
Section: Expression Of Cxcr6 By Cd4 and Cd8 T Cellssupporting
confidence: 89%
“…Furthermore, Unutmaz et al (38) showed that IL-15 stimulation increased the number of CXCR6 and CCR5 double-positive CD4 and CD8 T cells in vitro. These results suggest that CCR5 could also have an important role in T cell migration into the synovium.…”
Section: Discussionmentioning
confidence: 99%
“…CXCR6, the only known receptor for CXCL16, is also known as Bonzo, TYMSTR, and STRL33, and is a newly characterized chemokine receptor initially described as an HIV coreceptor expressed by a subset of memory/T effector cells, natural killer cells, and plasma cells (26)(27)(28)(29)(30). The present study directly addresses the participation of both CXCR6 and its ligand CXCL16 in leukocyte migration in RA.…”
mentioning
confidence: 85%
“…To study CXCR6 expression by different cells in the liver, we used Cxcr6 +/gfp mice in which the Cxcr6 coding region was replaced by GFP cDNA (23). GFP expression could be detected but also upon chronic liver injury (CCl 4 injury over 6 wk, MCD diet over 4 wk).…”
Section: Cxcr6 and Its Ligand Cxcl16 Are Up-regulated In Chronic Livementioning
confidence: 99%
“…In Cxcr6 +/2 and Cxcr6 2/2 mice, one or both alleles of Cxcr6 were replaced with GFP cDNA (15,23). All experiments were performed with animals at 6-8 wk of age under ethical conditions according to German legal requirements.…”
Section: Mouse Models and Phenotyping Analysesmentioning
confidence: 99%